2006
DOI: 10.1534/genetics.105.049205
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Synteny Between Arabidopsis thaliana and Species in the Asteraceae Reveal a Complex Network of Small Syntenic Segments and Major Chromosomal Rearrangements

Abstract: Comparative genomic studies among highly divergent species have been problematic because reduced gene similarities make orthologous gene pairs difficult to identify and because colinearity is expected to be low with greater time since divergence from the last common ancestor. Nevertheless, synteny between divergent taxa in several lineages has been detected over short chromosomal segments. We have examined the level of synteny between the model species Arabidopsis thaliana and species in the Compositae, one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The current study demonstrates that these COSII genes can also be used for comparative mapping across plant families-at least for the closely related plant families Solanaceae (tomato) and Rubiaceae (coffee). Understanding the modes and consequences of genome evolution across higher level taxa (such as families) may provide new insights into angiosperm diversification (Timms et al 2006). The current study, comparing the genomes of coffee and tomato, represents one of the few cases in which synteny could be well-deciphered across plant families.…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrates that these COSII genes can also be used for comparative mapping across plant families-at least for the closely related plant families Solanaceae (tomato) and Rubiaceae (coffee). Understanding the modes and consequences of genome evolution across higher level taxa (such as families) may provide new insights into angiosperm diversification (Timms et al 2006). The current study, comparing the genomes of coffee and tomato, represents one of the few cases in which synteny could be well-deciphered across plant families.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rice genome sequence has been used to facilitate map-based cloning in wheat and barley [25]. Unfortunately, while comparative analyses have revealed extensive co-linearity between closely related taxa [26][27][28], the length of conserved regions decreases dramatically with increasing evolutionary distance [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The rearrangement events in the evolutionary history of the genus Arabidopsis has been outlined by examining the level of synteny between the linkage maps of the Arabidopsis species and the Arabidopsis genome sequence (Yogeeswaran et al 2005;Hansson et al 2006). The major chromosomal rearrangements between Arabidopsis and Asteraceae (Timms et al 2006) and the structural divergence of the genic regions between Arabidopsis and Brassica (Suwabe et al 2006;Town et al 2006) also have been demonstrated by using the complete Arabidopsis reference sequence.…”
mentioning
confidence: 99%